2022
DOI: 10.1371/journal.pone.0266124
|View full text |Cite
|
Sign up to set email alerts
|

Identification of host transcriptome-guided repurposable drugs for SARS-CoV-1 infections and their validation with SARS-CoV-2 infections by using the integrated bioinformatics approaches

Abstract: Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) is one of the most severe global pandemic due to its high pathogenicity and death rate starting from the end of 2019. Though there are some vaccines available against SAER-CoV-2 infections, we are worried about their effectiveness, due to its unstable sequence patterns. Therefore, beside vaccines, globally effective supporting drugs are also required for the treatment against SARS-CoV-2 infection. To explore commonly effective repurposable drugs for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 149 publications
0
21
0
Order By: Relevance
“…In a study by Ahmed et al, a microarray dataset consisting of 10 and 4 PBMC samples of patients with SARS-CoV-1 infection and healthy controls, respectively was analyzed to find hub genes and remarkable signaling pathways in SARS-CoV-1 infection. The repurposable drugs for SARS-CoV-1 infections were then identified and validated for the treatment of SARS-CoV-2 infections (Ahmed et al 2022 ). Furthermore, Mosharaf et al analyzed an RNA-seq dataset consisting of 35 lung tissue samples infected with SARS-COV-2 (case) and 5 control samples to find differentially expressed genes (DEGs).…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Ahmed et al, a microarray dataset consisting of 10 and 4 PBMC samples of patients with SARS-CoV-1 infection and healthy controls, respectively was analyzed to find hub genes and remarkable signaling pathways in SARS-CoV-1 infection. The repurposable drugs for SARS-CoV-1 infections were then identified and validated for the treatment of SARS-CoV-2 infections (Ahmed et al 2022 ). Furthermore, Mosharaf et al analyzed an RNA-seq dataset consisting of 35 lung tissue samples infected with SARS-COV-2 (case) and 5 control samples to find differentially expressed genes (DEGs).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that TFs (FOXC1, YY1, GATA2, SREBF1 and FOXL1) were associated with CXCR4, CXCL1, COL6A3, COL1A2 and ITGA6 and miRNAs (hsa-mir-1-3p, hsa-mir-26b-5p, hsa-mir-29b-3p, hsa-mir-105-5P and hsa-mir-4781-5P) were closely regulated with THBS2, SOX9, THY1, COL1A2 and TIMP. In previous bioinformatics analyses, Ahmed, Islam, and Lu Lu et al found FOXC1, YY1, GATA2, and FOXL1 are significant TFs for COVID-19 (6,49,50). Pharmacological studies have also found that SREBF1, as a key regulator of lipid-metabolizing enzymes connected closely with the procession of AH, is the transcription factor most activated by several effective antiviral drugs in vitro and may become A pivot therapeutic spot for both AH and COVID-19 (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the regulatory relationship between TFs (FOXC1, YY1, GATA2, PPARG and FOXL1) and genes (FCGR1B, BCL6, CD1D, MS4A4A and LTF), as well as miRNAs (hsa-mir-27a-3p, hsa-mir-26a-5p, hsa-mir-124-3p, hsa-mir-146a-5p and hsa-mir-20a-5p) and genes ( SOCS3 , BCL6 , CXCR4 , and TNFSF13B ) that may play important roles in COVID-19 and sepsis. In previous bioinformatics analysis, Ahmed ( 72 ) and Islam et al. ( 73 ) both found that FOXC1, YY1, GATA2, and FOXL1 are important TFs for COVID-19.…”
Section: Discussionmentioning
confidence: 99%